2016
DOI: 10.4168/aair.2015.8.1.32
|View full text |Cite
|
Sign up to set email alerts
|

GIS-based Association Between PM10 and Allergic Diseases in Seoul: Implications for Health and Environmental Policy

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. Purpose:The role of PM10 in the development of allergic diseases remains controversial among epidemiological studies, partly due to the inability to control for spatial variations in large-scale risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Despite extensive research that shows a correlation between indoor air pollution and aggravation of asthma [4]- [6], providing a personalized risk assessment in real-time based on indoor air quality is still at an infant state. In [7], [8], a static relationship between the indoor air quality and the asthma attack is shown.…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive research that shows a correlation between indoor air pollution and aggravation of asthma [4]- [6], providing a personalized risk assessment in real-time based on indoor air quality is still at an infant state. In [7], [8], a static relationship between the indoor air quality and the asthma attack is shown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ambient PM 2.5 has become increasingly present in the surrounding air and significantly involved in human health, particularly in regard to respiratory tract diseases, as it can reach the bronchial tubes and deep regions of the lung [ 7 ]. Reference cohort studies in which participants are monitored for decades have discovered that smaller particles such as PM 2.5 have more adverse effects on human health than larger particles [ 4 , 8 , 9 , 10 ]. Additionally, epidemiological investigations into contamination, especially ambient air pollution, indicated that the PM is not only correlative with the exacerbation of cardiovascular diseases and respiratory systemic inflammation impacts but also the progression of inflammatory skin diseases [ 11 ] such as atopic dermatitis (AD) [ 12 , 13 , 14 ], acne, psoriasis, and allergic reactions [ 9 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the air pollution factors, PM 2.5 , NO 2 and CO were positively correlated with asthma in multiple regions. To our knowledge, there was no consensus among various studies on the air pollutants that affect the onset of asthma [11,15,18,[48][49][50]. Although the relationship between asthma and exposure to PM 2.5 has been frequently measured, reported conclusions have not been consistent [42].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between meteorological factors and air pollution on asthma deserves further study. Uniform policy interventions may not work due to regional difference in environmental factors for diseases [49], and it is essential to formulate differentiated prevention policies for different regions.…”
Section: Discussionmentioning
confidence: 99%